DESIGNING AND VALIDATING A PROBLEM-BASED LEARNING GAMIFICATION MODEL TO ENHANCE TEACHING COMPETENCIES AMONG PROSPECTIVE ELEMENTARY ISLAMIC SCHOOL TEACHERS - Wiku Aji Sugiri; Rizki Amelia; Sigit Priatmoko; Agus Mukti Wibowo; Tsaniyah Nafi'ah (JMIE (Journal of Madrasah Ibtidaiyah Education), 2026)
This research aimed to develop a Problem-Based Learning Gamification (PBLG) model that is valid and practical for prospective Madrasah Ibtidaiyah (Islamic Elementary School) teachers. The study employed a Research and Development (R&D) methodology. The developed model was rigorously validated by experts to assess its theoretical foundation, syntactic clarity, and component suitability. Expert validation results have indicated that the model has achieved a very high validity level of 98.12% (categorized as Highly Valid). The PBLG model has been proven to possess a strong theoretical basis and logical syntax, effectively integrating all stages of Problem-Based Learning (PBL) with significant gamification elements designed to enhance student motivation and active engagement. This model is academically sound and holds the potential to serve as an innovative instructional reference to support the development of prospective teachers' competencies within a problem-based learning context.